PENGELOLAAN PEMANFAATAN RUANG DI KAWASAN GUNUNG BROMO DAN SEKITARNYA SECARA BERKELANJUTAN DI KECAMATAN PONCOKUSUMO - ASYIAWATI, YULIA (Jurnal Perencanaan Wilayah dan Kota, 2014)
Indonesia consists of 514 districts / cities, one of which is Malang located in East Java province. Malang regency has the potential of Natural Resources is very abundant. Poncokusumo sub-district is one of the districts in Malang Regency has a variety of potential, ranging from agriculture and nature. One very famous natural attraction is Mount Bromo. Mount Bromo is one mainstay of tourism in the district of Malang Regency Poncokusumo. As is known, in 2010, Mount Bromo erupted and resulted in tremendous impact for the communities around Mount Bromo both in economic and environmental terms. Then in early 2011, there were concerns about local economic and environmental potential problems in the long term among residents in the area around Mount Bromo, especially in areas that are in Malang. The purpose of this study is to develop the concept of sustainable management of the space utilization in the region of Mount Bromo Poncokusumo District of Malang. This study included into the quantitative descriptive research type. The descriptive terms are included on the condition of the District of Poncokusumo be viewed from the potential and the problems they have. Quantitative analysis is supported by using the form of secondary data collection and primary distribution of open questionnaire. There are two questionnaires, the questionnaire 15 people and 15 questionnaires were distributed to visitors who do Pocokusumo the District community and the visitor Mount Bromo and field observation method is ground check Based on this research can be concluded that the potential possessed by the District Poncokusumo directed to development of the region by increasing the strategies undertaken: (1) Development Zone Main Commodity (KAPUK) horticulture; (2) The development of the excellent potential include industrial, food crops, plantations and tourism with prioriyas the cultivation of horticultural crops dengna concept agropolitan; (3) Utilization of space area by setting the cropping of 8443 Ha, tourism activities amounted to 7,431 ha and Land woke 3322.32 Ha (4) Cooperation among stakeholders and the public in environmental management accented with custom customs Tengger